Pengaruh Environment, Social, and Governance, dan Financial Distress terhadap Tax Aggressiveness di Indonesia: CEO Gender sebagai Variabel Moderasi - Agustini, Yassinta; Azwardi; Mukhtaruddin (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aimed to identify the effect of environment, social, and governance, and financial distress on tax aggressiveness in Indonesia, with ceo's gender as a moderating variable. Agency theory, legitimacy theory, and upper echelon theory are used as the main frameworks. Data was collected from the annual reports of 31 consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during 2012-2021. Panel data regression with a random effect model approach is used to test and analyze hypotheses. The results show that ESG has a negative and significant effect on tax aggressiveness. Financial distress has a positive and significant effect on tax aggressiveness. CEO gender as a pure moderator strengthens the relationship between ESG and tax aggressiveness. However, CEO gender does not moderate the relationship between financial distress and tax aggressiveness.